Language and identity politics a cross-Atlantic perspective - Spati, Christina (Berghahn Books, 2016)
In an increasingly multicultural world, the relationship between language and identity remains a complicated and often fraught subject for most societies. The growing political salience of questions relating to language is evident not only in the expanded implementation of new policies and legislation, but also in heated public debates about national unity, collective identities, and the rights of linguistic minorities. By taking a comprehensive approach that considers both the inclusive and exclusive dimensions of linguistic identity across Europe and North America, the studies assembled here provide a sophisticated look at one of the global era's defining political dynamics.